Baubiologie : Kriterien und architektonische Gestaltung - Ece, Nurgül (Basel : Birkhäuser, 2018)
Health and environmental compatibility are the focus of society. The book shows how the built environment can be aesthetically modern and at the same time healthy and environmentally friendly. It bridges the gap between architecture as a creative task and building biology thinking. Building biology is the study of the holistic interactions of man and his built environment. It combines building culture with ecology and disciplines such as chemistry, biology, geology and psychology. On the model of the Institute for Building Biology + Sustainability (IBN) building biology criteria and approaches are explained in detail. Numerous other current projects illustrate how these have been implemented in a responsible, healthy and thus sustainable architecture.
Frontmatter -- Inhalt -- Vorwort -- Ein Buch über Baubiologie -- Einführung in die Baubiologie -- Das Leuchtturmprojekt der Baubiologie -- Wohnbauten -- Fachwerkhaus Haingraben Liederbach am Taunus, Deutschland -- Wohn- und Werkstattgebäude in einer alten Torfremise Schechen, Deutschland -- Haus Ritter-Reumiller Andelsbuch, Österreich -- Strohhaus Dornbirn, Österreich -- Casa C Reckingen, Schweiz -- Haus für Julia und Björn Egg, Österreich -- Haus aus Holz Neumarkt in der Oberpfalz, Deutschland -- Maison Marly Marly-le-Roi, Frankreich -- Designhaus Haussicht Erkheim, Deutschland -- Öffentliche Bauten -- De Potgieter School Amsterdam, Niederlande -- Erweiterung Friedensschule und Feuerwache Schwäbisch Gmünd, Deutschland -- RHS Peter Buckley Learning Centre Rosemoor, Devon, England -- Kindertagesstätte Ecolino Pfaffenhofen an der Ilm, Deutschland -- Kinderkrippe Pollenfeld Pollenfeld, Deutschland -- Gewerbliche Bauten -- Herbafarm Bodrum, Türkei -- Hörger Biohotel Tafernwirtschaft Hohenbercha, Deutschland -- Almrefugio Neumarkt in der Oberpfalz, Deutschland -- Casa Salute Margreid, Südtirol -- Italien -- Betriebsgebäude Artis Berlin, Deutschland -- Omicron Campus Klaus, Österreich -- Weiterführende Informationen -- 25 Grundregeln der Baubiologie -- Wohnbauten Baubiologische Bewertung -- Wohnbauten Baubiologische Bewertung -- Öffentliche Bauten Baubiologische Bewertung -- Gewerbliche Bauten Baubiologische Bewertung -- Bildnachweis -- Dank -- Impressum
In German.
eBooks on EBSCOhost
Keywords: Architecture -- Human factors; Architecture -- Environmental aspects; Architecture, Modern -- 21st century -- Themes, motives; Architecture -- Facteurs humains; Architecture -- Aspect de l'environnement.; Architecture -- 21e siècle -- Thèmes, motifs; Methods & Materials; Design; ARCHITECTURE; Professional Practice; Construction; TECHNOLOGY & ENGINEERING; Architecture -- Environmental aspects; Architecture -- Human factors; Architecture, Modern -- Themes, motives; 2000-2099; Electronic books